Enemies ebook A history of the fbi. - Weiner, Tim (2012)
The hidden history of the FBI and its hundred-year war against terrorists, spies, and anyone it deemed subversive—including even American presidents.   NEW YORK TIMES  BESTSELLER • NOW A SHOWTIME ORIGINAL DOCUMENTARY SERIES   “Turns the long history of the FBI into a story that is as compelling, and important, as today’s headlines.”—Jeffrey Toobin, author of  American Heiress   Enemies  is the first definitive history of the FBI’s secret intelligence operations, from an author whose work on the Pentagon and the CIA won him the Pulitzer Prize and the National Book Award.   We think of the FBI as America’s police force. But secret intelligence is the Bureau’s first and foremost mission. The FBI’s secret intelligence and surveillance techniques have created a tug-of-war between national security and civil liberties, a tension that strains the very fabric of a free republic.  Enemies  is the story of how presidents have used the FBI to conduct political warfare—and how it has sometimes been turned against them. And it is the story of how the Bureau became the most powerful intelligence service the United States possesses. Named One of the Best Books of the Year by  The Washington Post,  New York  Daily News,  and  Slate “Pulitzer Prize–winning author Tim Weiner has written a riveting inside account of the FBI’s secret machinations that goes so deep into the Bureau’s skulduggery, readers will feel they are tapping the phones along with J. Edgar Hoover. This is a book that every American who cares about civil liberties should read.” —Jane Mayer, author of  Dark Money “Outstanding.” — The New York Times “Absorbing . . . a sweeping narrative that is all the more entertaining because it is so redolent with screw-ups and scandals.” — Los Angeles Times “Fascinating.” — The Wall Street Journal “Important and disturbing . . . with all the verve and coherence of a good spy thriller.” —The New York Times Book Review “Exciting and fast-paced.” — The Daily Beast